Principle Characteristics in Firms’ Competitiveness Endeavour: Use of Managerial and Strategic Reasoning Technics for Small & Medium Enterprises (SMEs) - Christos Lemonakis; Alexandros Garefalakis; Georgios Xanthos; Nikolaos Sialveras (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to study the characteristics of competitiveness in firms’ sectors of the Greek manufacturing industry, based on firm-level accounting and qualitative data attempting to identify key issues regarding Greek SMEs. An unbalanced data set of 407 Greek manufacturing SMEs is implemented, covering the period of 2003-2011 with the use of a multivariate regression model (EGLS) with explanatory variables characterizing firms’ operational activity. Although considerable empirical work has been done on this subject, research on the topic is limited and non-existent for Greece. An Index is developed in order to measure competitiveness characteristics in the Greek SMEs. The method to determine these characteristics in Greek manufacturing SMEs is novel using factors related to knowledge management, information technology, innovation in comparison with accounting data presenting main competitiveness characteristics especially in the during the crisis period .